The relationship between co-curricular leadership course and students' interpersonal skills at IIUM - Amisah (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This research explored the effectiveness of the Co-Curricular Leadership and Management (CCLM 2051) course on students' interpersonal skills and practice of interpersonal skills as perceived by undergraduate students from the Kulliyah of Education (KOED) at the International Islamic University Malaysia (IIUM). The study also attempted to find out the significant differences in the perceived effectiveness of CCLM 2051 on students' interpersonal skills as well as the practice of interpersonal skills based on their gender and year of study. The relationship between the effectiveness of the Co-Curricular Leadership and Management course and students' practice of interpersonal skills was investigated in this study. A purposive sampling technique was used to select 156 KOED undergraduate students who had taken the CCLM 2051 course in semester 1, 2016/2017. The collected data were analysed by using descriptive analysis (frequencies and percentages), T-test, ANOVA and Pearson Correlation. The results revealed that the majority of the students believed that CCLM 2051 certainly developed their interpersonal skills to a high level in respect of leadership, communication and problem solving skills. Similarly, the result of students' practice of interpersonal skills also indicated a high level of practice in all of these aforementioned skills. The T-test analysis showed that there was no significant difference in perceptions of all variables between male and female students except for the interpersonal communication skills practice. The ANOVA results revealed that there was no significant difference in all of the variables in respect of the students' year of study. Lastly, the result confirmed that there was a significant relationship between the course and students' practice of interpersonal skills. The lessons offered in the course will be beneficial for all undergraduate students to know the importance of CCLM 2051 in developing their interpersonal skills and the students would frequently practise interpersonal skills in their daily interactions.